2008
DOI: 10.1007/s00406-008-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual sensory processing deficits in Schizophrenia and their relationship to disease state

Abstract: Context Visual Evoked Potential (VEP) abnormalities have been a fairly consistent finding in patients with schizophrenia, and it has been suggested that electrophysiological markers of early sensory processing may be useful as trait markers for the illness, and for development as potential diagnostic measures. Objective Clear amplitude reductions in the occipital P1 component of the VEP (~100 ms), have been repeatedly demonstrated in patients with schizophrenia. Here, we investigated whether the extent of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
59
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 71 publications
9
59
2
1
Order By: Relevance
“…P100 amplitude was greater under ketamine than under placebo, which went against our prediction that the pattern observed in schizophrenia (8,(10)(11)(12)59,63) would be replicated. There are several potential ways to interpret our unexpected finding .…”
Section: P100 Effectcontrasting
confidence: 60%
See 2 more Smart Citations
“…P100 amplitude was greater under ketamine than under placebo, which went against our prediction that the pattern observed in schizophrenia (8,(10)(11)(12)59,63) would be replicated. There are several potential ways to interpret our unexpected finding .…”
Section: P100 Effectcontrasting
confidence: 60%
“…Koychev et al (13) reported Q3 that P100 amplitude predicted performance during a visual WM task in healthy control subjects but was reduced in patients with early-onset schizophrenia. These P100 effects in patients were demonstrated to be independent of drug dosage or symptom severity (8). Based on these and other data, it has been suggested that cognitive deficits in schizophrenia could involve abnormal sensory (i.e., bottom-up) processing (9).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…PSZ have been found to demonstrate deficits in ERPs elicited from WM tasks [17][18][19] and tasks probing sustained attention [20][21][22][23][24], among others; similar deficits have been observed in first-degree relatives of people with the disorder [22,25,26]. More recently, EEG research has examined oscillatory activity in the brain associated with WM.…”
mentioning
confidence: 85%
“…Þizofrenin erken döne-minde vizuel proçeslerde defisitin tespit edilmiþ olmasý, daha sonraki çalýþmalarda dopaminin retinada modülatör olarak majör rol oynadýðýnýn gös-terilmesi, þizofreni hastalarýnda retinal dopaminin azalmýþ olmasý ve fizyopatolojiden sorumlu mekanizmanýn bu þekilde açýklanmasý gibi nedenlerden dolayý psikiyatride OKT'nin ilk kullanýmý þizofreni hastalarýnda olmuþtur (19). Daha sonra diðer psikiyatrik hastalýklarla (Bipolar bozukluk, major depresyon, anksiyete bozukluklarý gibi) ilgili çalýþmalar yapýlmýþtýr (Tablo-1).…”
Section: Okt Ve Psikiyatriunclassified